2022
DOI: 10.17707/agricultforest.68.3.07
|View full text |Cite
|
Sign up to set email alerts
|

Structure Components and Yielding Capacity of Camelina Sativa in Ukraine

Abstract: The results of three-year research on the influence of different fertilization levels and foliar fertilization with micronutrients and growth regulators on the formation of structure elements and yielding capacity of Camelina sativa variety Hirsky are presented, their parameters in the process of plant vegetation has been defined. The influence of mineral fertilizers and micro-fertilizers on the elements composing the structure and formation of Camelina sativa seed yield on lowfertile sod-podzolic soils of Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Yielding capacity level is determined both by number of seeds per plant and by weight of 1000 seeds (Domaratskiy et al, 2022). The weight of 1000 seeds is a varietal characteristic, but it depends on the influence of various factors (Hryhoriv et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Yielding capacity level is determined both by number of seeds per plant and by weight of 1000 seeds (Domaratskiy et al, 2022). The weight of 1000 seeds is a varietal characteristic, but it depends on the influence of various factors (Hryhoriv et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The highest percentage of solid biomass use is observed in Finland. Ukraine has significant potential for the use of biomass for energy purposes, and all the necessary prerequisites for the widespread adoption of this renewable energy source [Juodka et al, 2022;Riaz et al, 2022;Hryhoriv et al, 2022]. During martial law, the impact of the energy situation has a negative impact not only on the economy, ecology and well-being of Ukrainian citizens, but also on dependence on imported energy.…”
Section: Introductionmentioning
confidence: 99%
“…During martial law, the impact of the energy situation has a negative impact not only on the economy, ecology and well-being of Ukrainian citizens, but also on dependence on imported energy. This becomes a prerequisite for Ukraine to actively consider alternative energy sources [Ryzhuk et al, 2002;Heletukha et al, 2014;Hryhoriv et al, 2022). According to the calculations, there are significant potential opportunities for the production of energy plant bioresources in Ukraine.…”
Section: Introductionmentioning
confidence: 99%
“…A plenty of studies have shown that the impact of effective microorganisms on plant organisms is extremely high (Talaat 2019;Jalal et al, 2020;Karbivska et al, 2020;Chaudhary et al, 2021). And it's not just plant yields (Raymond et al, 2021;Sousa et al, 2021;Khanna et al, 2019) or biometric properties (Gao et al, 2020;Hussain et al, 2021;Bada, 2022), but also a qualitative indicator such as chlorophyll content (Fitriatin et al, 2021;Kerubo et al, 2021;Kots et al, 2022;Hryhoriv et al, 2022). This also raises issues regarding…”
Section: Introductionmentioning
confidence: 99%